Self-compassion, positive body image, and eudaimonic well-being among Malaysian young adults - Teoh, Ping Hooi; Intan Hashimah Mohd Hashim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Self-compassion can potentially contributes to more positive body image and consequently eudaimonic well-being. Yet, limited researches has focused on the relationship between self-compassion and positive body image especially in the context of Malaysia. This study examined the association between self-compassion, positive body image, and eudaimonic well-being. A sample of 200 Malaysian young adults aged between 19 to 28 years old completed an online survey consisted of Self-Compassion Scale (SCS), Body Appreciation Scale-2 (BAS-2), and Psychological Well-Being Scale (PWB). Results indicated that self-compassion was positively related to positive body image (r= .43), positive body image had a significantly positive and strong association with eudaimonic well-being (r= .77), and self-compassion was positively correlated with eudaimonic wellbeing (r= .64). Findings highlight the importance of self-compassion and positive body image as positive traits that can contribute to well-being.